Fan pleasure and profit: Use-value, exchange-value, and one-sixth scale action figure customization - Godwin, Victoria L. (Journal of Fandom Studies, The, 2016)
Abstract One-sixth scale action figure fans complicate existing fan studies models, which emphasize cultural or social capital over economic capital, and which minimize or erase fan activities involving potential profit to focus instead upon gift economies. One-sixth scale action figure customization and other material fan practices offer productive examples of how multiple fandoms incorporate both pleasure and profit, use-value and exchange-value, into their fan practices, and how they explain or justify such practices to those within and outside their fan communities. Customizers emphasize their creations’ use-value over exchange-value in three specific ways. First, customizers create items not offered by any company. Second, they create affordable alternatives to expensive official merchandise. Third, their projects remedy inferior aspects of officially licensed merchandise. Customizers modify existing products or create their own if they cannot find or afford desired items of appropriate quality. These justifications offer insights into how multiple other fandoms likewise frame any commercial efforts as emphasizing use-value over exchange-value. Such constructions of fan practices ward against legal and ethical complications of using licensed texts, characters, and/or merchandise as a base or inspiration for one’s own creative efforts.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qZnMuNC4xLjM3XzE